Farm factors associated with increased free fatty acids in bulk tank milk - Hannah M. Woodhouse; Stephen J. LeBlanc; Trevor J. DeVries; Karen J. Hand; David F. Kelton (Journal of Dairy Science)
ABSTRACT: Elevated concentrations of free fatty acids (FFA) in bulk tank milk are a milk quality concern in the dairy industry. Hydrolysis of triacylglycerols (TAG) yields FFA, and milk with ≥1.20 mmol FFA/100 g of milk fat is associated with undesirable characteristics, such as off-flavor, rancidity, reduced foam stability, and inhibited cheese-milk coagulation. Research on FFA is limited and absent in North America, but research out of European regions indicates that high FFA are multifactorial. This study aimed to identify farm-level FFA risk factors in Canadian dairy herds. A cross-sectional study was conducted on 293 Canadian dairy farms in Ontario (n = 238) and British Columbia (n = 55). Over 2 yr, selected farms were visited once to complete a survey, assess milking systems, and gather data on the diet of lactating cows. Bulk tank FFA values for each farm 15 d before and 15 d after the research visit were obtained from the corresponding province's milk marketing board. Using these values, a monthly FFA average was calculated for each farm and used as the outcome variable. Seventy-one farms were tiestall, 109 were freestall with milking parlors, and 113 were freestall with automated milking systems (AMS). The mean bulk tank FFA was 0.84 mmol/100 g of fat (SD = 0.40, range 0.26 to 3.67), and 10% (n = 29) of herds had an elevated monthly average FFA (≥1.20 mmol/100 g of fat). In the final multivariable linear regression model, milking frequency ≥3×/d (times per day) compared with <3×/d was associated with a greater FFA concentration in AMS (β = 0.27, 95% CI: 0.12, 0.41) and tiestall milking systems (β = 1.17, 95% CI: 0.76–1.59). Regardless of milking frequency, none of the parlor farms visited had FFA ≥1.20 mmol/100 g of fat. For farms milking ≥3×/d, not changing the milk filter at least 2×/d was associated with greater FFA concentrations (β = 0.27, 95% CI: 0.10, 0.44). The absence of pre-cooling was also associated with higher FFA levels (β = 0.16, 95% CI: 0.02, 0.3). The final model adjusted R2 of 29% indicates that more factors associated with bulk tank milk FFA still need to be identified, which may include seasonal, milk composition, and individual cow factors.